A new single step synthesis of copper phthalocyanine green using microwave irradiation effects in functionalisation of C−H bonds in aromatic rings. Issue 3 (2014) - ,; ,; ,; ,
Abstract : Purpose – The paper introduces a new method for single step synthesis of copper phthalocyanine green pigment using microwave irradiation to activate C−H bonds on the aromatic rings that are possible by creation of chlorine radicals. The aims of this study are to investigate the possibility of high‐efficiency product reaction, removing acidic wastewater, time optimization, and maximizing number of chlorine on aromatic rings.Design/methodology/approach – The paper presents a new synthesis technique, which does not have the problems of the conventional methods. Microwave irradiation is used as a chemical reaction initiator by creation of chlorine radicals in saturated aqueous solution of sodium chloride and C−H bond activation on aromatic rings. The approach yields to a high quality of product, uniform particle size distribution, high efficiency and an environmental friendly procedure.Findings – The paper introduces the use of suitable materials and water solvents in chemical reactions under microwave radiation at low temperatures. This shows that the microwave irradiation activates C−H bonds on aromatic rings and creates chlorine radicals at the same time, which results in relatively fast reaction of synthesis copper phthalocyanine green.Research limitations/implications – The ammonium molybdate catalyst, which is used in this method, should be weighed carefully. The effects of transition metals on chemical reactions in the presence of microwave irradiation can also be chlorinated other unsaturated bonds.Practical implications – The method develops a simple and practical solution to improve the synthesis of phthalocyanine green pigment.Originality/value – The synthesis method of copper phthalocyanine green pigment is novel. CuPhcCl16 has numerous applications in industrial.